2022
DOI: 10.1093/aesa/saac023
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Five Warm Season Diptera Species in Estimating the Post-Mortem Interval

Abstract: The accurate estimation of the time of death (Post-Mortem Interval, PMI) is of great importance when reconstructing the actual events at a crime scene following the recovery of a body. The reliability of the PMI is vital to validate witness statements and suspect alibis. The PMI estimation based on insects collected from remains relies on two fundamental principles. Firstly, the development of an insect is proportionate to its surrounding environmental condition, and secondly, colonization by insects and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 125 publications
0
11
0
Order By: Relevance
“…In contrast, we found that L. cuprina required two more days to complete larval development on beef liver than on chicken or beef meat. Bambaradeniya et al (2023) observed somewhat slower development of L. cuprina on pig liver than on pig or beef muscle tissue and suggested that this was due to biochemical and structural differences in the tissue types. It is also worth noting that the species as well as type of host tissue can affect development times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we found that L. cuprina required two more days to complete larval development on beef liver than on chicken or beef meat. Bambaradeniya et al (2023) observed somewhat slower development of L. cuprina on pig liver than on pig or beef muscle tissue and suggested that this was due to biochemical and structural differences in the tissue types. It is also worth noting that the species as well as type of host tissue can affect development times.…”
Section: Discussionmentioning
confidence: 99%
“…flies are among the most important blow flies used in forensic entomology due to their frequent occurrence on human cadavers (Smith 1986). Because larvae of the Australian sheep blow fly, L. cuprina (Wiedemann), are among the first insects to arrive at a corpse, their presence and age is used to estimate the postmortem interval (PMI) (Bambaradeniya et al 2023). Moreover, larvae of L. cuprina are commonly used as maggot therapy to treat wounds (Paul et al 2009, Tantawi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, after this period, fly eggs, larval, and pupal specimens become one of the most reliable indices for the age determination of a carcass [21,22]. This is achieved by three methods: (1) calculating the accumulated degree day/hour units, (2) referring to life history tables, and (3) using species-specific isomegalen/isomorphen curves [23]. In addition, the minPMI in advanced stages of decomposition can be estimated by assessing the succession patterns of flies and other carrion-associated invertebrates, although this is generally less accurate [24].…”
Section: Forensic Entomology For Crime Scene Investigationsmentioning
confidence: 99%
“…Adult-level identification has a greater certainty in correct species determination, and they are well-described in taxonomic keys [145]. When rearing dipteran species in an insectary, they should be confined in insect cages and provided ad libitum with food, water, and oviposition substrates [17,23].…”
Section: Rearingmentioning
confidence: 99%
“…This is because its species are common, widely distributed, abundant, and are generally the first colonizers of a dead body. In many cases, they have the ability to detect a corpse from great distances [1][2][3][4][5][6]. Although Calliphoridae are ubiquitous, the abundance and colonization times of specific species may vary depending on the environmental conditions where a corpse is found.…”
Section: Introductionmentioning
confidence: 99%